Heavy manual work throughout the working lifetime and muscle strength among men at retirement age. Issue 4 (19th February 2016) - Walker-Bone, K; D'Angelo, S; Syddall, H E; Palmer, K T; Cooper, C; Coggon, D; Sayer, A A
Abstract : Introduction: Reductions in heavy manual work as a consequence of mechanisation might adversely impact muscle strength at older ages. We investigated the association between grip strength at retirement age and lifetime occupational exposure to physically demanding activities. Grip strength is an important predictor of long-term health and physical function in older people. Methods: Grip strength (maximum of three readings in each hand) was measured in men from the Hertfordshire Cohort Study at a single examination when their mean age was 65.8 (SD 2.9) years. Associations with lifetime occupational exposure (ascertained by questionnaire) to three activities (standing/walking ≥4 h/day; lifting ≥25 kg; and energetic work sufficient to induce sweating) were assessed by multivariable linear regression with adjustment for various potential confounders. Results: Complete data were available from 1418 men who had worked for at least 20 years. After adjustment for age, height and weight, those with longer exposures to walking/standing and heavy lifting had lower grip strength, but the relationship disappeared after further adjustment for confounders. Working at physical intensity sufficient to induce sweating was not significantly associated with grip strength. Conclusions: We found no evidence that physically demanding occupational activities increase hand grip strength at normal retirement age. Any advantages of regular physical occupational activity may have been obscured by unmeasured socioeconomic confounders.